Ocenjevanje prevalence nekaterih kroničnih bolezni in stanj v posameznih upravnih enotah regije Celje - Govc Eržen, Jana (Zdravstveno varstvo, 2004)
Aim. The aim of the research was to assess the prevalence of several chronic diseases (myocardial infarction, stroke, angina pectoris, increased blood pressure, musculoskeletal diseases, chronic respiratory diseases) in individual administrative units of the Celje region. Methods. The study was conducted as part of the national research project in 2001. In the Celje region, the questionnaire was sent to 2,310 randomly chosen individuals, aged 25 to 64 years. The prevalence of individual chronic diseases, grouped for clearer presentation, is expressed in %. Results. The response rate, calculated on the basis of the returned questionnaires, was 61.9%. The prevalence of individual groups of chronic diseases in the administrative units varies largely, with the average regional prevalence exceeding the national one. A very high prevalence was established for musculoskeletal diseases (35%), as well as for hypertension (19.3%) and some chronic cardiovascular diseases (11.7%) Conclusion. The established differences in theprevalence of chronic non-contagious diseases between the regions studied need further investigation. Appropriate measures will have to be taken to reduce the observed differences.
Keywords: bolezni gibal; cardiovascular disease; Celje; kardiovaskularne bolezni; pljučne bolezni; prevalenca